Nonlinear dynamics of mood regulation in unaffected first-degree relatives of bipolar disorder patients - A, Ortiz; K, Bradler; J, Garnham; C, Slaney; S, McLean; M, Alda (Journal of affective disorders, 2019)
BACKGROUND: Mood regulation is a complex and poorly understood process. In this study, we aimed to analyze the underlying dynamics of mood regulation in unaffected first degree relatives of patients diagnosed with bipolar disorder using time-series analysis. METHODS: We recruited 30 unaffected first-degree relatives of bipolar disorder patients. Participants rated their mood, anxiety and energy levels using a paper-based visual analog scale; they recorded their sleep and life events as well. Participants provided information on these variables over a three month period, twice per day. We compared their data using Box-Jenkins time series analysis with data from 30 healthy controls (HC) and 30 euthymic bipolar patients (BD) to obtain information on the autocorrelation and cross-correlation of the series, and calculated entropy for mood, anxiety and energy series. RESULTS: We analyzed 14,980 data points: 5200 in the healthy control group; 4970 in the bipolar group and 4810 in the unaffected relatives group. There were no significant differences between groups in terms of age, sex or education levels. Using Kolmogorov-Smirnov test, we found that individual measures were normally distributed in the whole sample (D = 0.23, p > 0.1). Autocorrelation functions for mood in all groups are governed by the ARIMA (1,1,0) model, which means that current values in the series are related to one previous point only. In terms of entropy for the mood series, unaffected relatives and bipolar patients showed lower values [mean (SD) : 1.028 ± 0.679; 1.042 ± 0.680], respectively, compared to healthy controls [(1.476 ± 0.33); F (2,74) = 4.39, p < 0.01]. The same case was seen in the energy series, with lower values in the unaffected relatives and bipolar patient groups [mean (SD) : 1.644 ± 0.566; 1.511 ± 0.879], respectively, compared to healthy controls [2.230 ± 0.531; F(2, 75) = 7.89, p < 0.001]. LIMITATIONS: Low resolution for the visual analog scale. CONCLUSIONS: Using nonlinear analyses, we found that the underlying structure of mood regulation in unaffected relatives is undistinguishable from the one found in bipolar patients. Compared to healthy controls, both bipolar patients and their unaffected relatives showed lower entropy levels, which is in keeping with a more rigid system, not as flexible to cope with the demands of a changing environment.
Keywords: afekt; Time-series; Self-Control; Humans; Case-Control Studies; lidé středního věku; úzkost; Nonlinear; studie případů a kontrol; sebekontrola; nelineární dynamika; Cyclothymic Disorder; Female; dospělí; Bipolar disorder; Mood regulation; lidé; Anxiety; Affect; bipolární porucha; Adult; vizuální analogová stupnice; ženské pohlaví; Male; Middle Aged; Unaffected relatives; Bipolar Disorder; Visual Analog Scale; mužské pohlaví; Nonlinear Dynamics; cyklotymní poruchy